Influence of the structure of the cation of ionic liquids on the vapor pressure and osmotic coefficients in their binary mixtures with 1-propanol - Eugénia A. Macedo (2012)
The osmotic (f) and activity coefficients and vapor pressures of binary systems containing the primary alcohol 1-propanol and 1-alkyl-3-methylpyridinium ionic liquids, CnMpy+ with n = 2, 3, 4, and the IL 1,1-butylmethylpyridinium, C4Mpyr+,all of them with the anion bis(trifluoromethylsulfonyl)imide, NTf2 -, were determined at 323.15 K using the vapor pressure osmometry technique. The f and vapor pressure depressions increased as the alkyl chain of the cation of CnMpyNTf2 increased. The ion-interaction model of Extended Pitzer model of Archer was successfully used to correlate the experimental data, obtaining standard deviations < 0.037. This is an abstract of a paper presented at the CHISA 2012 - 20th International Congress of Chemical and Process Engineering and PRES 2012 - 15th Conference on Process Integration, Modelling and Optimisation for Energy Saving and Pollution Reduction (Prague, Czech Republic 8/25-29/2012).